Xylanase and xylo- oligosaccharide prebiotic improve the growth performance and concentration of potentially prebiotic oligosaccharides in the ileum of broiler chickens. Issue 1 (2nd January 2020) - Craig, A. D.; Khattak, F.; Hastie, P.; Bedford, M. R.; Olukosi, O. A.
ABSTRACT: 1. The objective of this study was to investigate the effect of supplementing broiler diets with xylanase or xylo- oligosaccharide (XOS) on growth performance, the concentration of non-starch polysaccharide (NSP) hydrolysis products in the ileum and concentration of short chain fatty acids (SCFA) in the caeca of broiler chickens. 2. In total, 500 male Ross 308 broilers were used in this 29-day (d) study. The treatments were organised into a 2 × 2 plus 1 factorial arrangement consisting of two additives (xylanase or XOS) at two levels (low or high) plus a control treatment with no additives. This gave five treatments with 100 birds in each treatment group. The diets were slightly deficient in protein by 20 g/kg and energy by 1 MJ/kg. 3. On d 14 and 28, two birds per pen were euthanised, the caeca content collected and analysed for short chain fatty acid (SCFA) concentration. On d 29, six birds per pen were euthanised and ileal digesta were collected and analysed for the concentration of NSP fractions. 4. On d 14, caecal acetic acid, iso-butyric acid, iso-valeric acid, n-valeric acid and total SCFA concentrations were significantly greater (P ≤ 0.05) when diets were supplemented with XOS compared with xylanase. 5. Ileal concentration of arabinose, galactose and glucuronic acid (GlucA2) were significantly greater (P ≤ 0.05) in the insoluble NSP fraction when diets were supplemented with a high level of xylanase, compared with the control treatment. Ileal concentration of fructose was significantly greater (P ≤ 0.05) in the water soluble NSP when a high level of xylanase or low level of XOS were included in the diet compared with the control. 6. It was concluded that xylanase and XOS had similar effects on NSP concentration and SCFA in the caeca, although there was little effect on performance. This observation demonstrated further benefits of xylanase supplementation in wheat-based broiler diets beyond digesta viscosity reduction and the release of extra nutrients.